2019
DOI: 10.2147/ahmt.s200801
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect and features of information technology-based interventions on self-management in adolescent and young adult kidney transplant recipients: a systematic review</p>

Abstract: IntroductionAdolescent and young adult periods are characterized by increased risk-taking, impulsive behavior, and nonadherence issues, which makes it equally challenging for patients and their health care professionals. Health information technology (IT) has the potential to empower patients.ObjectiveDetermine the effects and features of IT-based interventions for self-management of adolescents and young adults in kidney transplant recipients.Materials and MethodsA comprehensive survey was done on Medline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Interventions to structure medication-taking are needed, since adherence is worse on the weekend [ 49 ]. Among young adults, information technology-based interventions show promise in improving care process self-management outcomes, but their effect on clinical outcomes is less certain [ 50 ]. Furthermore, developmentally appropriate interventions will need to be considered for this age-range.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to structure medication-taking are needed, since adherence is worse on the weekend [ 49 ]. Among young adults, information technology-based interventions show promise in improving care process self-management outcomes, but their effect on clinical outcomes is less certain [ 50 ]. Furthermore, developmentally appropriate interventions will need to be considered for this age-range.…”
Section: Discussionmentioning
confidence: 99%
“… Computer systems, which enable the patient to record and transmit data and through the internet. Multi-component tools, which is a combination of more than one tool from the above mentioned tools [ 27 29 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Multi-component tools, which is a combination of more than one tool from the above mentioned tools [ 27 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mobile health can serve as an adjuvant method for delivering health education information, sending reminders to patients to take their medicine, and implementing online education. A systematic review indicated that information technology-based interventions such as mobile health/personal digital assistants (PDAs), computer systems, and multi-components have the potential to improve selfmanagement in adolescents and young adult kidney transplant recipients (Ganjali et al, 2019). However, due to the limited number of studies and absence of sufficient data, our meta-analysis did not find significant results demonstrating that interventions together with mobile health or electronic monitoring were more effective than the routine intervention.…”
Section: Summary Of Main Findingsmentioning
confidence: 64%